STRUKTUR KOMUNITAS KUPU-KUPU PADA AREA WANA WISATA AIR TERJUN COBAN RAIS DI BATU - Rahayu, Sofia Ery; Tuarita, Hawa (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
The purpose of this study is not only to determine the structure of a community that consist of abundance, diversity, evenness, and richness of butterflies but also to observe the abiotic factors at CobanRais. The research conducted classified into exploratory descriptive. Butterfly sampling conducted in CobanRais (along 2.5 km) in June-September 2013, with walking transect technique. Animals sampling was conducted from 08.00 to 12.00 a.m. The butterflies that had collected were identified based on morphological characters. The results showed that the butterflies were found are 64 species and belonging to the 6 family that is Papilonidae, Nymphalidae, Pieridae, Hesperidae, Lycanidae, and Rindinidae. The species most commonly found in CobanRais is Cyrestislutea with abundance values are 23%. Diversity of butterfly community in CobanRais is high with a value of 3.373. Evenness of butterfly communities in locations observation is high because close to 1 with a value of E = 0.811 and Butterfly species richness in CobanRais is high with a value R = 11.36.Â Keywords: butterfly, community structure, Coban Rais